The effect of Ai Chi aquatic therapy on individuals with knee osteoarthritis: a pilot study - So, Billy C.L.; Kong, Iris S.Y.; Lee, Roy K.L.; Man, Ryan W.F.; Tse, William H.K.; Fong, Adalade K.W.; Tsang, William W.N. (Journal of Physical Therapy Science, 2017)
[Purpose] To examine the efficacy of Ai Chi in relieving the pain and stiffness of knee osteoarthritis and improving, physical functioning, proprioception and quality of life. [Subjects and Methods] Twenty-five persons with knee osteoarthritis completed 5 weeks Ai Chi practice (60 minutes per session, twice per week, 10 sessions in total). Knee pain and stiffness were measured before and after the intervention program. [Results] Significant improvements in pain, self-perceived physical functioning and self-perceived stiffness were observed after the Ai-Chi intervention. On average, no significant change in knee range of motion, 6-minute walk test distances or proprioception was observed. [Conclusion] A five-week Ai Chi intervention can improve the pain and stiffness of knee osteoarthritis and self-perceived physical functions and quality of life improvement. Ai Chi may be another treatment choice for people with knee OA to practice in the community.